Comparison of curiosity levels of physical education teachers to the teachers of other branches - Zehra Certel; Ziya Bahadır (Selcuk University, 2014)
It is thought that a teacher with a sense of curiosity is more effective in arousing sense of curiosity of his/her students. In this regard; the study aimed to determine curiosity levels of branch teachers, to explore whether or not their curiosity levels differed in terms of the variables of gender, age, professional seniority (length of service) and marital status and to compare curiosity levels of physical education teachers to the teachers of other branches. The study was conducted with 388 branch teachers who taught in Kayseri during the academic year of 2011-2012. As the data collection tool; Curiosity Index (CI-3) [which was developed by Ainley (1987) (cited by Fulcher, 2004) and Turkish version of which was made by Demirel and Coşkun (2009)] was used. For the data analyses; descriptive statistics methods such as frequency (n), percentages (%), arithmetical means and standard deviation were used in order to analyze descriptive personal information. In order to detect the differences; such non-parametric tests as Mann Whitney U test and Kruskal-Wallis test were employed because the data did not follow a normal distribution and homogeneity conditions were not obtained in the variables of gender, age, marital status, professional seniority (length of service). In light of the findings; it was found out that curiosity levels of those branch teachers who were aged between 23 and 30, female and single were higher and that curiosity levels of physical education teachers were lower than other branch teachers in Kayseri.